The Evolution of Social Mobility: Norway over the 20th Century - Tuomas Pekkarinen; Kjell G. Salvanes; Matti Sarvimäki (Institute for the Study of Labor (IZA), 2016)
This paper documents trends in social mobility in Norway starting from fathers born at the turn of the 20th century and ending with sons born in the 1970s. We measure social mobility with intergenerational income elasticities, associations between fathers' and sons' income percentiles, and brother correlations. All approaches suggest that social mobility increased substantially between cohorts born in the early 1930s and the early 1940s. Father-son associations remained stable for cohorts born after WWII, while brother correlations continued to decline. The relationship between fathers' and sons' income percentile ranks is highly nonlinear for the early cohorts, but approaches linearity over time. We discuss increasing educational attainment among low- and middle-income families as a possible mechanism behind these trends.
Keywords: I24; J08; 330; intergenerational mobility; education; sibling correlation